(untitled) (Literasi Nusantara, 2025)
This study examines online communities’ views on the alleged art theft by artificial intelligence (AI) on social media platform X, focusing on the lawsuit between Disney and Midjourney. The purpose of this study is to analyze how the general public discusses and positions the issue of AI copyright, and how they construct meanings related to creativity, originality, and ownership of works today. This study uses a qualitative approach with a case study method and is based on a constructivist paradigm, and applies the Critical Discourse Analysis model developed by Teun A. Van Dijk. Data were obtained through in-depth interviews with selected informants and observations of netizen conversations on platform X. The results show two main opposing views: those who view the use of AI as a violation of ethics and copyright that is detrimental to human creativity, and those who consider AI to be a natural technological innovation that supports the creative process. This study concludes that social media plays a role in the formation of meaning, where people actively discuss, debate, and negotiate their understanding of AI, copyright, and creativity.